New data on the phylogeny of Ariantinae (Pulmonata, Helicidae) and the systematic position of Cylindrus obtusus based on nuclear and mitochondrial DNA marker sequences. (12th November 2013) - Cadahía, Luis; Harl, Josef; Duda, Michael; Sattmann, Helmut; Kruckenhauser, Luise; Fehér, Zoltán; Zopp, Laura; Haring, Elisabeth
Abstract The phylogenetic relationships among genera of the subfamily Ariantinae (Pulmonata, Helicidae), especially the sister‐group relationship of Cylindrus obtusus, were investigated with three mitochondrial (12S rRNA, 16S rRNA, Cytochrome c oxidase subunit I) and two nuclear marker genes (Histone H4 and H3). Within Ariantinae, C. obtusus stands out because of its aberrant cylindrical shell shape. Here, we present phylogenetic trees based on these five marker sequences and discuss the position of C. obtusus and phylogeographical scenarios in comparison with previously published results. Our results provide strong support for the sister‐group relationship between Cylindrus and Arianta confirming previous studies and imply that the split between the two genera is quite old. The tree reveals a phylogeographical pattern of Ariantinae with a well‐supported clade comprising the Balkan taxa which is the sister group to a clade with individuals from Alpine localities. Additional lineages representing samples from southern Alpine localities as well as from Slovakia split from more basal nodes, but their relationships are not clearly resolved. To achieve more definitive conclusions concerning the geographical origin of Ariantinae, still more sequence data are needed to obtain a tree with better resolution of basal nodes. The genetic data also provided new insights concerning the genus Cepaea, which was used as one of the outgroup taxa. Cepaea vindobonensis is only distantly related to Cepaea nemoralis and Cepaea hortensis, the latter two being more closely related to Eobania vermiculata. Thus, in our tree, the genus Cepaea is paraphyletic.